Carob pulp syrup: A potential Mediterranean carbon source for carotenoids production by Rhodosporidium toruloides NCYC 921. (September 2018) - Martins, Vasco; Dias, Carla; Caldeira, João; Duarte, Luís C.; Reis, Alberto; Lopes da Silva, Teresa
Abstract: Carob pulp syrup (CPS) was used as carbon source to produce carotenoids from Rhodosporidium toruloides . To increase the carbon concentration in the growth medium aiming at the carotenoid production improvement, the CPS was concentrated and two different total sugar (TS) concentrations (195.6 g/L and 548.7 g/L) were studied. CPS 195.6 g/L TS contained 4.1 g/L and 0.7 g/L of hydroxymethyl furfural (HMF) and furfural, respectively. CPS 548.7 g/L TS contained 17.7 g/L of HMF and 1.2 g/L of furfural, respectively. >42% of metabolically active cells (with intact membrane and enzymatic activity) were detected throughout the course of the yeast cultivation on CPS 195.6 g/L TS. On the contrary, the proportion of metabolically active cells was always below 28% during the yeast cultivation on CPS 548.7 g/L TS. Nevertheless, the maximum carotenoid content and productivity (0.42 mg/g and 0.43 mg/Lh, respectively) were obtained when using CPS 548.7 g/L TS. Highlights: Carob pulp syrup (CPS) was used as carbon source in media formulation. CPS solutions with 195.0 and 548.7 g/L of total sugars were tested for yeast growth. Concentrated CPS (548.7 g/L) induced the highest stress level in the yeast cells. Concentrated CPS induced the highest biomass and carotenoids yeast production.